2013
DOI: 10.3201/eid1904.121198
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 10-Valent Pneumococcal Vaccine on Pneumonia among Children, Brazil

Abstract: Pneumonia is most problematic for children in developing countries. In 2010, Brazil introduced a 10-valent pneumococcal conjugate vaccine (PCV10) to its National Immunization Program. To assess the vaccine’s effectiveness for preventing pneumonia, we analyzed rates of hospitalization among children 2–24 months of age who had pneumonia from all causes from January 2005 through August 2011. We used data from the National Hospitalization Information System to conduct an interrupted time-series analysis for 5 citi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
89
1
10

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(107 citation statements)
references
References 27 publications
(26 reference statements)
7
89
1
10
Order By: Relevance
“…It is expected, therefore, a reduction in the number of CAP cases and its consequences, such as hospitalization and mortality, which was actually seen. This finding is similar to that of a study by Afonso et al15 reporting a reduction of pneumonia cases in cities where the coverage was over 95%, unlike the cities with lower coverage, such as São Paulo (75%) and Porto Alegre (85%), where such a reduction was not seen. In our study, as shown in Table 2, many municipalities showed vaccine coverage above 100%.…”
Section: Discussionsupporting
confidence: 91%
“…It is expected, therefore, a reduction in the number of CAP cases and its consequences, such as hospitalization and mortality, which was actually seen. This finding is similar to that of a study by Afonso et al15 reporting a reduction of pneumonia cases in cities where the coverage was over 95%, unlike the cities with lower coverage, such as São Paulo (75%) and Porto Alegre (85%), where such a reduction was not seen. In our study, as shown in Table 2, many municipalities showed vaccine coverage above 100%.…”
Section: Discussionsupporting
confidence: 91%
“…(4) In this sense, in 2010 the National Immunization Program included in the vaccination schedule 10-valent pneumococcal conjugate vaccine, which represented an important advance in Brazilian public health concerning prevention of invasive disease and other disease caused by S. pneumoniae. (17) However, it is worth to emphasizing that our study delineated tendencies of hospital morbidity related to bacterial pneumonia in 2000 to 2011, which did not permit to assess the effects of vaccination, from the two first months of life, throughout time series studies.…”
Section: Discussionmentioning
confidence: 99%
“…Estimates from time trend analyses have been more varied. For instance, a 13% reduction in clinical pneumonia in children <12 mo was found from a population-based surveillance study in Brazil (24), whereas estimates of ∼20% and 40% were found using administrative databases from Brazil and the United States, respectively (7,25). Aside from comparing estimates from time trend studies to randomized controlled trials, the best ground-truth estimate of vaccine impact that we can obtain is to quantify changes in morespecific categories of pneumococcal disease, where high-quality surveillance studies provide an estimate of the expected decline.…”
mentioning
confidence: 99%